White Matter Tracts Associated With Deep Brain Stimulation Targets in Major Depressive Disorder: A Systematic Review - Yu, Qun; Guo, Xinxia; Zhu, Zhoule; Feng, Chen; Jiang, Hongjie; Zheng, Zhe; Zhang, Jianmin; Zhu, Junming; Wu, Hemmings (Frontiers in Psychiatry, 2022)
Major depressive disorder (MDD) is a common psychiatric disorder that is recurrent and resistant to antidepressant medications and cognitive/behavioral therapy in a relatively high proportion of patients. Deep brain stimulation (DBS) has been proposed as a last-resort treatment and has shown potential antidepressant effects for MDD in multiple clinical trials. However, the clinical effects of DBS for MDD are inconsistent and suboptimal with 30-70% responder rates. The reasons are multifactorial, and one of the factors is that MDD is a heterogeneous neuropsychiatric disorder involving different neural networks, yet DBS targeting is not individualized. The currently used DBS targets include cortical and subcortical brain regions associated with different brain circuits. We propose that DBS targeting for MDD should be tailored based on implicated dysfunctional brain circuits for precise white matter tract (WMT) modulation to achieve better clinical effect. In this review, we summarize the currently used DBS targets for MDD and relevant diffusion tensor imaging (DTI) studies, and categorize abnormal WMT into different dysfunctional brain circuits, to present a taxonomy of DBS targets based on dysfunctional brain circuits modulation in MDD.